The concept and realisation of a socio-cultural network research model for the analysis of a dialectal shift - Čepaitienė, Agnė; Gudaitis, Aidas (Baltistica, 2022)
The article introduces the concept of a Geographic Information System (GIS) technology-based socio-cultural network research model, which is designed to analyse the mobility trends of communities and determine a dialectal shift. The performance of the model is illustrated by examining the shift of the primary and tertiary phonetic differential features of the Eastern Aukštaitian of Panevėžys (EAP) subdialect. The study material consists of statistical, geospatial, survey and linguistic data. The assessment of community mobility was based on the existing facilities of social infrastructure in the area of EAP as well as adjacent dialects. The coefficients of influence of the facilities on language were calculated on the basis of expert judgement. The socio-cultural network was modelled on the basis of shortest path analysis between 223 points of the Atlas of the Lithuanian Language and 1708 closest social infrastructure facilities. Language variation was determined on the basis of an analysis of the audio recordings of 48 respondents born between 1888 and 1997. The results reveal six large centres of influence in the EAP area as well as in the area of surrounding subdialects. The analysis shows that both the social infrastructure accessibility index and the coefficient of influence correlate statistically significantly with the settlement population, but the level of infrastructure does not have a significant impact on the overall variation in EAP features. The correlation between socio-economic factors and a linguistic shift is more pronounced — for example, in communities with a higher educational rate, a higher shift in EAP dialectal features is observed. Quantitative analysis of socio-cultural factors and linguistic investigation confirmed that local language variants used in the northern part of the EAP are viable and less affected than those in the southern EAP range.